The Cut that Scars: Exploring Female Genital Mutilation in Somalia with Reference to Select Texts (Indian Journal of Public Health Research & Development, 2020)
Female Genital Mutilation (FGM) is termed as a horrendous practice that causes harm to the female genitalorgans. Tracing its roots before the arrival of Abrahamic religions, the ritual that was originally a part ofAfrica has crossed boundaries and is practiced around the globe. With more than 3 million girls cut everyyear, United Nations has declared FGM as a ritual that needs to be curbed. Somalia is one country where theincidence of genital mutilation and its aftermath is very high. Most women in Somalia undergo the ritual ofcut to purify themselves. This paper looks into “type three cutting” (infibulation) in Somalia with the help ofthree works written by Somali authors-Hibo Wardere, Ayaan Hirsi Ali and Waris Dirie.
Keywords: Female Genital Mutilation, Tradition, Somali Writers, Violence